Implementation of Flip-Chip Microbump Bonding between InP and SiC Substrates for Millimeter-Wave Applications - Jongwon Lee; Jae Yong Lee; Jonghyun Song; Gapseop Sim; Hyoungho Ko; Seong Ho Kong (Micromachines, 2022)
Flip-chip microbump (μ-bump) bonding technology between indium phosphide (InP) and silicon carbide (SiC) substrates for a millimeter-wave (mmW) wireless communication application is demonstrated. The proposed process of flip-chip μ-bump bonding to achieve high-yield performance utilizes a SiO2-based dielectric passivation process, a sputtering-based pad metallization process, an electroplating (EP) bump process enabling a flat-top μ-bump shape, a dicing process without the peeling of the dielectric layer, and a SnAg-to-Au solder bonding process. By using the bonding process, 10 mm long InP-to-SiC coplanar waveguide (CPW) lines with 10 daisy chains interconnected with a hundred μ-bumps are fabricated. All twelve InP-to-SiC CPW lines placed on two samples, one of which has an area of approximately 11 × 10 mm2, show uniform performance with insertion loss deviation within ±10% along with an average insertion loss of 0.25 dB/mm, while achieving return losses of more than 15 dB at a frequency of 30 GHz, which are comparable to insertion loss values of previously reported conventional CPW lines. In addition, an InP-to-SiC resonant tunneling diode device is fabricated for the first time and its DC and RF characteristics are investigated.